(untitled) - Trew, Grant (Oxford, 2006)
Tactics for TOEIC Speaking and Writing Tests Pack is authorized by Educational Testing Service (ETS) and contains official TOEIC items. This complete preparation course will help students develop the necessary skills to do well on the new computer-based Speaking and Writing tests. It focuses on building the range and understanding of language use, and awareness of key-testing strategies needed to get a high score. The Pack includes a Student Book, Class Audio CDs, Key and a Tapescripts booklet.
Keywords: Test of English for International Communication,English language,English language; Examinations